Characteristics and outcomes of neurosurgical patients in an emergency hospital admission setting - Li, Yuehua; Chen, Wei (Frontiers in Neurology, 2025)
ObjectiveThis study aims to investigate the characteristics of patients admitted to the neurosurgery department in an emergency manner.MethodsA population-based, retrospective cohort study including consecutive patients admitted to the department of neurosurgery as emergency admissions in a non-profit tertiary care university hospital was conducted. Data on demographic information, clinical characteristics and outcomes were collected and evaluated. Patients were stratified into five disease groups (vascular disease, trauma, oncology, spine, and others) according to their main diagnoses at the time of admission.ResultsA total of 4,149 cases (median age 52 years, 54.5% male) were included in this study. Vascular disease was the most common reason for emergency admission (73.5%). Significant differences were found among the five disease groups in sex (P < 0.001), age (P < 0.001), surgery (P < 0.001), and season (P = 0.009) but not in the length of stay (P = 0.784). Multivariate logistic regression analysis identified male sex, older age, short length of stay, surgery not performed, and disease type (particularly trauma) as independently associated with in-hospital mortality.ConclusionsThere is demographic heterogeneity and clinical differences exist among neurosurgical patients admitted to the neurosurgery department as an emergency. In addition, male sex, older age, shorter length of stay, absence of surgery, and admission due to trauma emerged as independent predictors of higher in-hospital mortality.